A pilot study evaluating non‐contact low‐frequency ultrasound and underlying molecular mechanism on diabetic foot ulcers. Issue 6 (19th November 2012) - Yao, Min; Hasturk, Hatice; Kantarci, Alpdogan; Gu, Guosheng; Garcia‐Lavin, Silvia; Fabbi, Matteo; Park, Nanjin; Hayashi, Hisae; Attala, Khaled; French, Michael A; Driver, Vickie R
Abstract: Non‐contact low‐frequency ultrasound (NCLF‐US) devices have been increasingly used for the treatment of chronic non‐healing wounds. The appropriate dose for NCLF‐US is still in debate. The aims of this pilot study were to evaluate the relationship between dose and duration of treatment for subjects with non‐healing diabetic foot ulcers (DFUs) and to explore the correlation between wound healing and change of cytokine/proteinase/growth factor profile. This was a prospective randomised clinical study designed to evaluate subjects with non‐healing DFUs for 5 weeks receiving standard of care and/or NCLF‐US treatment. Subjects were randomly assigned to one of the three groups: application of NCLF‐US thrice per week (Group 1), NCLF‐US once per week (Group 2) and the control (Group 3) that received no NCLF‐US. All subjects received standard wound care plus offloading for a total of 4 weeks. Percent area reduction (PAR) of each wound compared with baseline was evaluated weekly. Profiles of cytokines/proteinase/growth factors in wound fluid and biopsied tissue were quantified to explore the correlation between wound healing and cytokines/growth factor expression. Twelve DFU patients, 2 (16·7%) type 1 and 10 (83·3%) type 2 diabetics, with an average age of 58 ± 10 years and a total of 12 foot ulcers were enrolled. Average ulcer duration was 36·44 ± 24·78 weeks and the average ABI was 0·91 ± 0·06. Group 1 showed significant wound area reduction at weeks 3, 4 and 5 compared with baseline, with the greatest PAR, 86% ( P < 0·05); Groups 2 and 3 showed 25% PAR and 39% PAR, respectively, but there were no statistically significant differences between Groups 2 and 3 over time. Biochemical and histological analyses indicated a trend towards reduction of pro‐inflammatory cytokines (IL‐6, IL‐8, IL‐1β, TNF‐α and GM‐CSF), matrix metalloproteinase‐9 (MMP‐9), vascular endothelial growth factor (VEGF) and macrophages in response to NCLF‐US consistent with wound reduction, when compared with control group subjects. This proof‐of‐concept pilot study demonstrates that NCLF‐US is effective in treating neuropathic diabetic foot ulcers through, at least in part, inhibiting pro‐inflammatory cytokines in chronic wound and improving tissue regeneration. Therapeutic application of NFLU, thrice (3) per week, renders the best wound area reduction.